Factors Influencing Farming Practices towards Nutrition Sensitive Agriculture in Southern Odisha - Nibedita Mishra, Nibedita Mishra; Satarupa Modak, Satarupa Modak; Chitrasena Padhy, Chitrasena Padhy; Akhila Badavath, Akhila Badavath (Indian Journal of Extension Education, 2025)
In order to alleviate food and nutrition insecurity, nutrition-sensitive agriculture places a strong emphasis on integrating agricultural interventions with nutrition goals. Understanding how attitudes and perception influences the nutrition practices and dietary choices is crucial for effective nutrition sensitive agriculture. The study explores how household practices influence the nutritional outcomes and factors affecting nutrition sensitive agricultural interventions aimed at improving people’s dietary patterns. This method seeks to enhance the quality and variety of diets in addition to increasing food production by acknowledging the connections between nutrition, agriculture, and health. Though there are varying perspectives and obstacles to overcome, nutrition-sensitive agriculture is generally seen favorably, with many acknowledging its potential to improve food systems. The present study was conducted in Gajapati and Rayagada districts of Odisha in 2024. Three blocks were selected from each district, totaling six blocks randomly, total of 20 respondents from each block selected by simple random sampling technique to form a total sample size were 120. Majority of respondents (53%) were having less favourable perception towards Nutrition Sensitive Agriculture with moderate (59%) attitude towards nutrition sensitive agriculture.